Cyanobacteria community status of two natural lakes (Pamvotida, Zazari) in Greece (2025)
Lortou, U., I. Nikolopoulou, A. Zacharioudaki, K. Aligizaki, K. Moschandreou, and V. Tsiaoussi. 2025. Cyanobacteria community status of two natural lakes (Pamvotida, Zazari) in Greece. Presentation in 13th International Conference of Toxic Cyanobacteria, ICTC13, Chania, Crete, 4-8 May 2025